Phytopathogenic micromycetes on alien plants from the publication «Black book of the flora of Belarus: alien harmful plants» - Poliksenova, Valentina D.; Khramtsov, Alexander K.; Hirilovich, Ivan S.; Lemeza, Nikolai A.; Sidorova, Svetlana G.; Stadnichenko, Marina A. (Experimental Biology and Biotechnology, 2021)
The 228 species of phytopathogenic micromycetes parasitising alien plants included in the publication «Black book of the flora of Belarus: alien harmful plants» (Minsk, 2020) were identified in the course of the conducted research. It was found that out of 322 plant species listed in this edition phytopathogenic micromycetes were found on 182 species (56.5 %). It is noted that among the phytopathogenic micromycetes only 92 species and intraspecific taxon (40.4 %) belong to the alien species of the Republic of Belarus. Obviously, these phytopathogens are highly specialised and currently parasitise only on these invasive plant species. The remaining 136 species and intraspecific taxon (59.6 %) affect both native and alien plant species.
Keywords: phytopathogenic micromycetes; alien plants; Belarus; micobiota